Evolução biológica na perspectiva de estudantes do ensino médio: das concepções espontâneas aos saberes escolares - Santos, Pâmela Mello dos (2017)
The significance of teaching Biological Evolution in High School has been justified by several studies showing the unifying and integrative role of this topic for the other biological subjects. In the present study, we addressed the conceptions of High School students on Biological Evolution at three different moments that we denominated Stage I, Stage II and Stage III. At the first Stage, we sought to identify the spontaneous conceptions on the formation of the current planet biodiversity of High School second-year students. Stage II occurred after students had had classes on the study topic and it was based on the use of cartoons presenting questions about Lamarckism, Natural Selection, Natural Selection and Adaptation, Natural Selection and Reproduction, Genetics, Natural Selection and Competition. Stage III encompassed the application of a questionnaire containing questions similar to those of the cartoons, one year after Stage II. From these three stages, we could recognize that students present some ideas about evolutionary matters even before classes on the theme and also identify the recurrent mistakes on the topic, which reflected ideas of common sense as, for example, the perception that Evolution occurs by necessity and for improvement. The lasting conceptions about the topic indicated that there is an understanding about acquired traits not being inherited; adaptation is not the same as becoming used to some environmental condition; competition can be inter or intraspecific, occurring due to many reasons; natural selection is related to a greater chance of surviving and reproducing; some similarities and some differences among organisms can be explained by variation in DNA; survival is influenced by several factors, but better-adapted individuals have greater chances to survive. Among the misconceptions that lasted are the disuse being responsible by the inherited atrophy of body’s parts and the dominance of a phenotype representing its frequency in a population. Some issues were unsatisfactorily understood, including the resistance to antibiotics and poisons, the origin of genetic variability and the time necessary to natural selection take place. The relevance of knowing these conceptions is in compliance with the importance of making a more meaningful teaching, where the topics can be understood in an integrated way.